Aplikasi Desain Motif Tenun Songket Bali - Nyoman Dewi Pebryani; Tjok Istri Ratna, C.S.; Putu Manik Prihatini (Institut Seni Indonesia Denpasar, 2022)
Songket weaving is an Indonesian cultural heritage that has been passed down from generation to generation. Every region in Indonesia has its own Songket weaving, depending on the region’s characteristics. Bali island is one well-known region in Indonesia for Songket weaving. In the past, Songket weaving in Bali was only made for caste members and the royal family. At that time, only people in the royal family were able to make Songket weaving. The songket weaving process in Bali was mainly performed using a weaving tool called cagcag. The songket weaving pattern (motif) was made using a sungkit technique—interlace between threads to create a motif. The making of the songket motif begins with arranging the thread according to the desired motif before the weaving process. Information about the motif was spread in Guun. In general, songket weaving in Bali island has tens to hundreds of Guun. The skills to break the desired motif into the Guun is quite a complicated process. Therefore, not many weavers master the process of making songket motifs. Most of the motif makers continue or imitate existing motifs. Currently, a motif maker who can make a motif from scratch is rare. In order to help break motifs into Guun, an in-depth understanding of the calculation of making songket motifs is required. Then, this understanding is transformed into an application that can help motif makers to visualize motifs into Guum. The design application will provide multiple benefits for the motif makers and serve as an effort of culture preservation by introducing a design application to make songket motifs for younger generations. Therefore, they are expected to contribute to making songket weaving motifs.